2005
DOI: 10.1592/phco.25.4.511.61033
|View full text |Cite
|
Sign up to set email alerts
|

Costs Associated with the Management of Overactive Bladder and Related Comorbidities

Abstract: This study quantifies the increased prevalence of and additional medical costs associated with related comorbidities in patients with OAB, emphasizing that the economic and clinical impact of OAB extends beyond the disease itself. Thus, management of patients with OAB should be of greater focus with both clinicians and health care payers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
1
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 24 publications
2
93
1
5
Order By: Relevance
“…In turn, increased medical requirements necessitated by either suboptimal treatment or potentially avoidable chronic disease sequelae lead to increased costs, increased health care utilization, and increased susceptibility to adverse drug reactions. [27][28][29][30][31][32][33][34][35][36] In a longitudinal cohort study conducted by Balkrishnan et al (2006), OAB patients experienced a 5.6% reduction in annual health care costs for every 10% increase in MPR. 36 By comparing across 6 chronic therapeutic areas, the present study confirms that room for improvement in drug persistence and adherence exists across a range of conditions.…”
Section: ■■ Conclusionmentioning
confidence: 99%
“…In turn, increased medical requirements necessitated by either suboptimal treatment or potentially avoidable chronic disease sequelae lead to increased costs, increased health care utilization, and increased susceptibility to adverse drug reactions. [27][28][29][30][31][32][33][34][35][36] In a longitudinal cohort study conducted by Balkrishnan et al (2006), OAB patients experienced a 5.6% reduction in annual health care costs for every 10% increase in MPR. 36 By comparing across 6 chronic therapeutic areas, the present study confirms that room for improvement in drug persistence and adherence exists across a range of conditions.…”
Section: ■■ Conclusionmentioning
confidence: 99%
“…11 Depression is strongly associated with OAB. [14][15][16] OAB patients become anxious in unfamiliar surroundings: they focus on and may be preoccupied with such concerns as locating the closest bathroom, looking for aisle seating, and estimating the amount of time until their next work break. 14,17 Embarrassment, frustration, anxiety, annoyance, depression, and fear of odor can have a negative impact on daily activities, such as travel, physical activity, interpersonal relationships, and sexual function, resulting in social isolation.…”
Section: Socioeconomic Burden Quality Of Life and Social Impactmentioning
confidence: 99%
“…9 In addition, it has been shown that the prevalence of depression in those with OAB is two-fold higher than in the general population (10.5% vs. 4.9%, respectively; p<0.0001). 10 At a societal level, OAB is associated with substantial healthcare costs. In Canada, the total excess cost attributed to OAB, excluding nursing care and lost productivity, was approximately $576 000 000 in 2009; this rose to over $640 000 000 when lost productivity was taken into account.…”
Section: Introductionmentioning
confidence: 99%